The Understanding of Temperament to Conquer Intrinsic Nature and to Modify Behaviour through Buddhist Principles based on Applied Mindfulness - Linphoo , Montree; Linphu, Phra Futrakul; Poonasron, Saard Poonasron (Journal of Humanities and Social Sciences Suratthani Rajabhat University, 2023)
This academic article explains the nature of unconsciousness and how it affects a person's behavior and way of life in the outside world. To permanently enhance creative behavior, it is imperative to modify the level of a personality root called "temperament," which is categorized into six types according to Buddhist principles and consists of the characters as follows: 1) lust (Rāga-carita), 2) hatred (Dosa-carita), 3) delusion (Moha-carita), 4) faith (Saddhā-carita), 5) intelligence (Buddhi-carita), and 6) speculation (Vitakka-Carita). Each person has mixed temperaments, but only one is marked. Each temperament has different characteristics in the forms of lifestyle, manner, strength, and weakness, including resolving methods. Buddhist principles present the methods through mindfulness practice and contemplation of the truths. If applying Buddhist principles of mindfulness to each temperament can change bad habits into good ones, it leads to a successful life.